Journal of Housing and the Built Environment (JSTOR)
The Journal of Housing and the Built Environment presents the refereed results of original scientific research, and new developments in policy and practice in the fields of housing, spatial planning, building and urban development. The aim is to give international exposure to recent developments, providing a forum for the exchange and discussion of new ideas. The journal benefits a diverse readership of scientists, specialists, practitioners and policy-makers in government and in organizations dealing with housing and urban issues.
Keywords: Architecture & Architectural History